2018
DOI: 10.1029/2018gl078577
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic Constraints of the 2017 Mw7.3 Sarpol Zahab, Iran Earthquake, and Its Implications on the Structure and Mechanics of the Northwest Zagros Thrust‐Fold Belt

Abstract: We reveal transient surface deformation following the 2017 Mw7.3 Sarpol Zahab (Iran) earthquake using Interferometric Synthetic Aperture Radar (InSAR) measurements. Based on the coseismic interferograms derived from the Advanced Land Observing Satellite‐2 (ALOS‐2) data, the preferred slip model of the earthquake has a centroid depth of 14.5 ± 4 km and suggests that a basement fault is most likely responsible for the 2017 earthquake in the northwest Zagros fold‐thrust belt zone. Two slip asperities with a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
62
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 32 publications
15
62
3
Order By: Relevance
“…The posterior mean model of the final cumulative slip is shown in Figure 4a. At first order, this solution is in agreement with previously published static models (Barnhart et al, 2018;Wanpeng et al, 2018). We infer a ∼50-km-long and ∼30-km-wide rupture, with a peak slip of 5.5 ± 0.5 m. One difference arises as previous models proposed that two distinct asperities ruptured during the earthquake.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The posterior mean model of the final cumulative slip is shown in Figure 4a. At first order, this solution is in agreement with previously published static models (Barnhart et al, 2018;Wanpeng et al, 2018). We infer a ∼50-km-long and ∼30-km-wide rupture, with a peak slip of 5.5 ± 0.5 m. One difference arises as previous models proposed that two distinct asperities ruptured during the earthquake.…”
Section: Resultssupporting
confidence: 92%
“…Although the subvertical plane is compatible with a back thrust fault that may exist in the region (Tavani et al, 2018) or with the reactivation of steep normal faults (Jackson, 1980), the shallow-dipping plane is in better agreement with receiver functions analysis (Paul et al, 2010) and the tectonic setting (e.g., Berberian, 1995;Vergés et al, 2011). Our optimal plane (351 • strike, 14 • dip, 13-km depth) agrees well with other studies using a similar grid search approach (Barnhart et al, 2018;Wanpeng et al, 2018). In the following, we will consider that the Ezgeleh earthquake occurred on our optimum shallow dipping plane.…”
Section: Estimation Of the Fault Planesupporting
confidence: 89%
See 2 more Smart Citations
“…3 on a shallow dipping within the Arabian crystaline basement, while afterslip concentrated up dip of the rupture zoned on the basal decollement. Using similar geodetic data, Feng et al, (2018) found two large-slip asperities with a maximum slip of 6 m at ~15 km depth. In this study, we use both C-band Sentinel-1 and L-band ALOS-2 data with multiple viewing geometries to generate the coseismic ground deformation maps.…”
Section: Accepted Manuscriptmentioning
confidence: 81%